A Dictionary of Accounting (Oxford Oxford University Press, 2010)
This best-selling dictionary includes more than 3,600 entries covering all aspects of accounting, including financial accounting, financial reporting, management accounting, direct taxation, indirect taxation, auditing, corporate finance, and accounting bodies and institutions. It includes feature entries on key areas--such as Bankruptcy Law and the FTSE share indexes--and its international coverage includes important terms from Australia, India, and Malaysia. 150 new entries have been added to this edition to reflect the very latest developments in the accounting profession, such as recent legislation, UK tax changes, and reliefs and allowances, including Entrepreneurs' Relief and Annual Investment Allowance. In addition, coverage of taxation, personal finance, and auditing has been increased. The volume also offers recommended web links for many entries, accessed and kept up to date via the Dictionary of Accounting companion website. With its authoritative and straightforward definitions and its wide-ranging coverage, this dictionary is essential for students and professionals in accounting and finance.
Keywords: Accounting